Two-stage total hip arthroplasty for patients with advanced active tuberculosis of the hip. Issue 1 (December 2016) - Li, Liangjun; Chou, Ke; Deng, Jianliang; Shen, Feng; He, Zhiyong; Gao, Shuguang; Li, Yusheng; Lei, Guanghua
Abstract Background Treatment of advanced active tuberculosis (TB) of the hip is confronted with great challenges. Although one-stage total hip arthroplasty (THA) is considered as a safe procedure for most patients by some authors, there are still exceptions. The purpose of this paper was to investigate the feasibility and effectiveness of two-stage THA for selected patients with advanced active TB of the hip. Methods Nine consecutive patients with advanced active tuberculous arthritis of the hip were reviewed in this study. Out of these nine patients, the hips of five were destroyed extensively with difficulties of thorough debridement at one operation, and the hips of the other four were detected of sinus tracts. Nine patients received the two-stage total hip arthroplasty (THA) protocol and the perioperative antituberculous medication between January 2008 and December 2013. During the first stage, a debridement was carried out after at least 2 weeks of antituberculous chemotherapy to remove abscesses and infected and necrotic tissues as thoroughly as possible, followed by antituberculous chemotherapy for a minimum of 3 months (average 4.2 months). During the second stage, hip prosthesis was implanted if the erythrocyte sedimentation rate (ESR) and the C-reactive protein (CRP) were normal and the wound was well healed. Antituberculous chemotherapy was continued for 6–9 months postoperatively to constitute a total duration of a minimum of 12 months after the first operation. The patients were then evaluated based on the reactivation of infection, the Harris hip score system, X-ray, ESR, and CRP. Results The average follow-up was 40 months (range, 18–72 months). No reactivation of TB or superimposed infection was observed in all patients. The ESR and CRP returned to the normal level with no liver injury. The average Harris hip score was increased from 35 (range, 15–55) preoperatively to 91.5 (range, 83–97) at the final follow-up. The X-ray film showed no prosthesis shift or loosening. Conclusions Two-stage THA is an alternative treatment option for patients with advanced active tuberculosis of the hip under some difficult conditions. The hip with sinus tracts or destroyed extensively with difficulties of thorough debridement at one operation may be regarded as indications.